2018
DOI: 10.1016/j.eururo.2018.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Comparing Open Radical Cystectomy and Robot-assisted Laparoscopic Radical Cystectomy: Oncologic Outcomes

Abstract: Of 118 patients randomly assigned to undergo radical cystectomy/pelvic lymphadenectomy and urinary diversion, half were assigned to open surgery and half to robot-assisted techniques. We found no difference in risk of recurring or dying of bladder cancer between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
153
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(165 citation statements)
references
References 30 publications
8
153
0
4
Order By: Relevance
“…Likewise, Bochner et al . reported that there were no significant differences in DFS or OS between ORC and RARC . However, in that randomized study, it appeared that the patient population was skewed toward earlier stage disease given the percentage of patients with organ‐confined disease .…”
Section: Rarcmentioning
confidence: 92%
See 4 more Smart Citations
“…Likewise, Bochner et al . reported that there were no significant differences in DFS or OS between ORC and RARC . However, in that randomized study, it appeared that the patient population was skewed toward earlier stage disease given the percentage of patients with organ‐confined disease .…”
Section: Rarcmentioning
confidence: 92%
“…In a recent prospective randomized trial comparing RARC with ORC, there were no statistically significant differences between the groups, even though the ORC group tended toward higher overall rates of distant recurrence as their first site of recurrence than the RARC group (27.6% and 16.7%, respectively; P = 0.077) . However, the ORC group showed significantly less local/regional recurrence than the RARC group (10.3% and 16.7%, respectively; P = 0.035) …”
Section: Rarcmentioning
confidence: 93%
See 3 more Smart Citations